Effect of Educational Intervention on the Knowledge of Nursing Students Regarding Dengue Fever: Knowledge of Nursing Students Regarding Dengue Fever - Mian, Nasar; Khanum, Sabiha; Ali Shah, Bakhtiyar; Aurangzeb, Muhammad; Anwar, Nasir; Sultan, Amir; Zeb, Akhter; Hussain, Shah (Pakistan Journal of Health Sciences, 2023)
Dengue (DEN-gee) fever is a tropical disease caused by a virus carried by mosquitoes. The virus can cause fever, headaches, rashes, and pain throughout the body. Objective: To determine the effect of educational program regarding dengue fever among 4th year nursing students in Peshawar Pakistan. Methods: This quasi-experimental study was conducted in Peshawar from October 2020 to March 2021. The study duration was six months. It was one group pre and post study design. The sample was collected through simple random sampling from 4th November 2020 to 4th December 2020. The sample size was 65; while the target population was fourth year nursing students in five different nursing colleges in Peshawar. Data analysis was performed through SPSS version 20. Results: In the pre-test, majority of the participant’s knowledge was average 72.3%, while the remaining participant’s knowledge were poor 27.7% regarding dengue fever. In post-test the level of knowledge of all the participants were good 100%. The mean knowledge score of pre-intervention was 16.98 with the SD of 2.88 whereas; the mean knowledge score of the post-intervention was 27.16 with the SD of 1.13. Similarly, the p-value was found statistically highly significant (p=0.001, t (64) = -27.914, CI 95%). Conclusion: The study concluded that interventional study may help to convey the knowledge from classroom to other nursing students, patients, homes, and friends.